A legal analysis of successful and problematic Build Operate and Transfer (BOT) projects in Malaysia - Markom, Ruzian; Engku Ali, Engku Rabiah Adawiah (Universiti Malaysia Sarawak, 2012)
The Malaysian government has adopted the Build Operate Transfer (BOT) project contractual arrangement for developing public infrastructure projects like highways and railways. In an effort to balance the economic and social needs of the community, the government has introduced a policy and legal framework to address the issue. The aim of this article is to study factors contributing to both successful and problematic BOT projects in Malaysia. The analysis reveals that there are common underlying factors contributing to the success of BOT projects such as: sound policy and regulatory framework, strong government support, clarity of project formulation and documentation, responsible sponsors and fair deals for all parties. On the other hand, the factors contributing to the problematic projects are individualised. Finally, steps to overcome the problems are elucidated to improve the efficiency and effectiveness of both BOT legal technique and privatisation in general.